LACTATION MANAGEMENT AGAINST NUTRITIONAL STATUS IN INFANT IN SUNGAI RAYA DALAM PRIMARY HEALTHCARE CENTER, KUBU RAYA REGENCY, WEST KALIMANTAN - Otik Widyastutik; Yeni Pratiwi; Abrori ,; Ratna , (Universitas Airlangga, 2021)
During the covid19 pandemic, malnutrition should be prevented. Nutritional status in infants may weaken their immunity, intelligence and productivity and arises their vulnerability to diseases and stunting during their development. The initial survey showed that in the working area of Sungai Raya Dalam Primary Healthcare Center, Kubu Raya District, West Kalimantan 60% of mothers have infants with malnutrition. This study aims to determine the relationship between lactation management (techniques, duration and frequency of breastfeeding) and the nutritional status of infants (0-12) months. This study used a case-control design. The research sample was 98 respondents (49 cases and 49 controls) selected by purposive sampling technique. The results showed that there was a significant relationship between mother's breastfeeding technique (p = 0.001; OR = 4.471; 95% CI = 1.882-10.620), duration of breastfeeding (p = 0.004; OR = 3.692; 95% CI = 1.578-8.638), and the frequency of breastfeeding (p = 0.009; OR = 3.257, OR = 1.422-7.459) with nutritional status of infants aged 0-12 months in the working area of Sungai Raya Dalam Primary Healthcare Center. Reflecting on the study, it is recommended for the health workers to provide counseling materials related to the techniques, duration and frequency of breastfeeding, and encourage mothers to get the required knowledge about them using Kartu Menuju Sehat (KMS) or Health Cards.Keywords: lactation management, malnutrition, breastfeeding technique, duration, frequency